2011
DOI: 10.2320/matertrans.m2011191
|View full text |Cite
|
Sign up to set email alerts
|

Using the Low-Cost Waste Materials for Heavy Metals Removal from the Mine Wastewater

Abstract: The possibility of application of low-cost and easily available materials such as cardboard or sawdust for the heavy metals removal from the acid mine water was investigated. The sawdust was obtained from oak and fir-wood. Those materials were tested on the real acid mine wastewater that contained copper, iron, zinc, nickel, and manganese in the concentrations above the maximal allowed level. The adsorption degrees of those elements were investigated. The results were shown that the iron was mechanically remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…It is used as a low-cost waste material to remove heavy metal from mine wastewater [35]. However, in the current study no amphoteric solubility properties were observed in response to the variation of pH between 6 and 8.…”
Section: Effect Of Metal Adsorption To Particulate Mattermentioning
confidence: 38%
“…It is used as a low-cost waste material to remove heavy metal from mine wastewater [35]. However, in the current study no amphoteric solubility properties were observed in response to the variation of pH between 6 and 8.…”
Section: Effect Of Metal Adsorption To Particulate Mattermentioning
confidence: 38%
“…Therefore, pH experiments were limited up to pH 5 in order to be sure that only the biosorption mechanism is responsible for the removal of Cu 2+ ions. The range of the sorbate in model aqueous solutions (20-200 ppm) corresponds to the actual content of Cu 2+ in industrial wastewater (Markovi c et al, 2011).…”
Section: The Range Of the Parametersmentioning
confidence: 99%
“…Esses referidos autores constataram que em valores de pH de 7,70 a 7,94 a remoção de Fe foi acima de 99%. 32 Num estudo conduzido por Kumar foi observada que a máxima retenção de Fe do efluente sintético utilizando bagaço de cana-de-açúcar como meio filtrante foi de 40%. 33 A ARS bruta já apresentava concentração de Fe abaixo dos 15 mg L -1 estabelecidos na Resolução CONAMA 430/2011, 3 e assim permaneceu após o tratamento com filtração.…”
Section: Concentração De Metais No Efluente Do Filtro Orgânicounclassified